Польское в Крымской элегии Нины Берберовой - Mianowska, Joanna (Acta Polono-Ruthenica, 2018)
This academic paper explores Polish themes in the novel The Crimean Elegy written by a well-known novelist and memoir writer, the first wave Russian emigrant in the 20th century, Nina Berberova. Polish themes in the prose of Russian emigrants, the representatives of the first wave of the Russian Emigration in the 20th century, often appear as reminiscences (the prose of A. Kuprin, R. Gul, B. Zaytsev and others). In Berberova’s The Crimean Elegy a famous opera singer Julia Bolesławowna Z. goes to the Crimea, the land of her childhood and adolescence, in order to calm her strained nerves and, although it is a foreign land, she finds it safe, where the church and the memories associated with it play a leading role. As it turned out, the church, the sound of barrel organs, the chants, Shubert’s Ave Maria performed by Julia Bolesławowna Z. appeared to be a treasure trove of the highest moral values for Berberova’s heroine. And even though the government has changed its appearance on the Crimea and before the church stood now a freckled, snub-nosed “man with a gun”, he would not dare to enter the house of God. A Pole, a catholic, with her music and the performance of Shubert’s Ave Maria, she has revived the passion of the deceased, who once prayed on this land to Black Madonna of Częstochowa or to Our Lady of Kraków.